AKIBAT PENGHENTIAN BILATERAL INVESTMENT TREATY (BIT) INDONESIA – BELANDA YANG DILAKUKAN SECARA SEPIHAK OLEH INDONESIA - Eka Husnul Hidayati; Suhaidi Suhaidi; Mahmul Siregar; Jelly Leviza (USU LAW JOURNAL, 2017)
ABSTRACT The Indonesia-Netherlands BIT has been terminated since July 1st, 2015. The intention to terminate has been submitted by Indonesia to the Netherlands on March, 2014. The validity of the termination was questioned by investors, businessmen, and international lawyers, given the ground of the termination undertaken by Indonesian Government was to protect Indonesia’s national interests. The research, which is a descriptive-analytical normative legal research, tends to examine the basic regulations of BIT set under Indonesian and international legal system as well as analyzing the termination undertaken by Indonesia unilaterally from both perspective of Indonesian national law and international law. The research is also describing the consequences arising from the termination. Keywords: bilateral investment treaty, unilateral termination,